PEMBIASAAN DZIKIR AL MA’SURAT DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SMP ISLAM TERPADU AL AFIF PALEMBANG - Febriyani, Riskiya; Nurlaila, Nurliala; Halimatussakdiah, Halimatussakdiah (PAI RAFAH, 2024)
This This study examines the habit of dhikr Al Ma'tsurat in shaping the religious character of students at the Al Afif Integrated Islamic Junior High School Palembang. The purpose of this study was to answer the question of how the implementation of habituation of dhikr Al Ma'tsurat in shaping the religious character of students, the supporting and inhibiting factors of habituation of dhikr Al Ma'tsurat in shaping the religious character of students at SMP Islam Terpadu Al Afif Palembang, and the efforts of teachers in shaping religious character. through the habit of dhikr Al Ma'tsurat at the Al Afif Integrated Islamic Junior High School Palembang. The results showed that the students of Al Afif Integrated Islamic Junior High School had implemented religious characters in their daily lives, but in the implementation of Al Ma'tsurat dhikr activities, the school had to make various creative efforts to familiarize students with Al Ma'tsurat dhikr, so that the implementation became effective and efficient in accordance with indicators of religious character that are in line with the school's vision and mission.